Applying Analisis Fungsi Manajemen dalam Meningkatkan Mutu Layanan Rawat Inap di RS Nurhidayah Bantul: Applying Of Management Function to Improve the Quality Of Inpatient Services at Nur Hidayah Hospital Bantul - Isnaini, Safira Ayu; Firman, Firman; Saffanah, Amadini Maisun (International Journal of Healthcare Research, 2022)
Background: The challenges of private hospitals in implementing quality inpatient services are influenced by governance with limited resources. This can be seen in the achievement of inpatient service quality indicators at Nur Hidayah Hospital which fluctuate, for example the incidence of nosocomial infections (HAIs) as many as 154 incidents of nosocomial infections per year. The compliance indicator for efforts to prevent the risk of injury due to patient falls has met the standards but officers have not been compliant in documenting reporting. In addition, compliance with specialist doctor visiting hours and compliance with hand washing of officers are inconsistent. This situation illustrates that the management function in controlling the quality of inpatient services is very much expected and needed. Methods: This study used a cross-sectional design. The sampling technique was a non-probability sample, and the number of respondents was 31 nurses at Nur Hidayah Hospital. The unit of analysis of this study was the inpatient unit, the statistical test used was the chi square test to see the relationship between managerial functions and the quality of inpatient services. Results: The practice of management functions implemented by the head of the unit in controlling the quality of hospital inpatient services includes adequate planning functions (51.6%), adequate organizing functions (58.1%), adequate direction (58.1%), adequate supervision (41.9%), adequate control (41.9%) and adequate evaluation (45.2%). Statistically, all of the above management functions have a relationship to the quality of inpatient services with a significance value of p<0.05. Conclusion: The head of the unit needs to maintain and encourage more consistent and sustainable innovation efforts in controlling the quality of inpatient services.